Efektivitas ekstrak daun mengkudu (Morinda citrifolia) untuk meningkatkan respon imun non spesifik dan kelangsungan hidup ikan Mas (Cyprinus carpio) - Sri Herlina (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
One of the problems in the cultivation of carp (Cyprinus carpio) is disease attack caused by bacteria and viruses. Disease prevention and prevention efforts can be done by increasing the immunity of fish. This study aims to determine the dose of noni (Morinda citrifolia) leaf extract effective to improve non-specific response and survival of carp. Experimental study using Completely Randomized Design (CRD) with 3 treatments and 3 replications with treatment A (0 g / kg of feed), treatment B (5 g / kg of feed), C treatment (10 g / kg of feed) The addition of 5g / kg of feed showed the best result to increase leukocyte and survival among other treatments during 28 days maintenance .